Rancang Bangun Fitur Chatbot Customer Service Menggunakan Dialogflow - Jansen Wiratama; Samuel Ady Sanjaya; Victor Ilyas Sugara (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2022)
The quality of providing customer service channels is very influential on customer satisfaction. To keep customer satisfaction, it is necessary to have a good interaction from customer service to the customer. In this case, PT Dian Prima Jayaraya is one of the companies that utilize Solo's application product as a medium for customer service. The development of the Solo application makes the application's features more complex and makes it difficult for users to do activities in the application. Customer service has a role in accommodating questions and answering difficulties experienced by users. The number of incoming questions is quite large, so that the existing customer service team cannot answer. Ignored or unanswered questions can lower the level of customer satisfaction. Therefore, we need a system that can help optimize customer service in a Chatbot to minimize unanswered customer questions. A chatbot is a service powered by rules and artificialintelligence, which the user interacts with through a chat interface. The Chatbot will be built on an iOS prototype application and use the NLP (Natural Language Processing) platform, namely Dialogflow. This platform will process and scan every question given by the customer.